PENGARUH PEMIKIRAN ISLAM REVOLUSIONER ALI SYARI’ATI TERHADAP REVOLUSI IRAN - Nugroho, Anjar (Profetika Jurnal Studi Islam, 2014)
The Islamic revolution of Iran happened in 1979 shows as the most realexample of how people power could take over the tyranny era and monarchy systemlasting for 200 years in Iran. Their collective awareness is caused by the source ofreligion awareness (Shia Islam) that has been up dated. Ali Syari?ati became thebrightened intellectual actor, that is as the phenomenon of the dictator grinding thepeople in Syah Pahlevi?s Government. Syari?ati, then, acted as the pioneer of radicalideas about revolution and Islam which taken from Shia teachings as the source, thathave been mixed with the tradition of the third World Revolutionary and Marxism. AliSyari?ati succeed developing revolutionary Islam ideology in which, then, becomes thebasis of people?s collective awareness opposing the era of Syah Pahlevi?s Government.According to Ali Syari?ati?s idea, Islam is a freedom and emancipation ideology. accordingto him this idea of Islam is progressive and revolutionary, sourcing to one system offaith, that is; tauhid. If the tauhid based on Ali Syari?ati?s idea is the unity of God,Human and Environment, so the condition of community having social discrimination,injustice and the arbitrary can be classified as syirk.It is the opposing of tauhid. Theoffer of Syari?ati?s idea and Islam ideology become the bridge or the fourth way of deadlock ideology pre-revolutionary opposition movements. They are Secular-nationalist,Communist-Marxist and Islam Fundamentalism. Finally, this Syari?ati?s ideology leadsImam Khomeini to be accepted as the revolutionary leader.Key Words: iran revolution; Shia, and freedom.Revolusi Islam Iran yang terjadi pada 1979 adalah contoh paling nyata,bagaimana kekuatan massa mampu menumbangkan rezim tiranik sekaligus sistemmonarki yang sudah berumur 200 tahun di Iran. Kesadaran kolektif massa itu disebutsebutbersumber dari kesadaran agama (Islam Syi?ah) yang sudah diperbaharui. AliSyari?ati muncul menjadi sosok intelektual tercerahkan adalah fenomena kekuasaanrezim Syah Pahlevi yang otoriter dan menindas.Syari?ati lalu tampil sebagai peloporgagasan-gagasan radikal tentang Islam dan revolusi yang bersumber dari ajaran Syi?ahyang sudah dicangkokkan dengan tradisi revolusioner Dunia Ketiga dan Marxisme.Ali Syari?ati berhasil membangun ideologi Islam revolusioner yang kemudian menjadibasis kesadaran kolektif massa menentang kekuasaan rezim Syah. Dalam pemikiranSyari?ati, Islam adalah sebuah ideologi emansipasi dan pembebasan.Pandangan IslamAli Syari?ati yang progresif dan revolusioner bersumber pada satu sistem keyakinanyaitu tauhîd.Jika tauhîd dalam pandangamanusia dan alam semesta, maka kondisi masyarakat yang penuh diskriminasi sosial,ketidakadilan, dan kesewenang-wenangan dapat dikategorikan sebagai Syirk, lawandari tauhîd. Tawaran pemikiran dan ideologi Islam Syari?ati menjadi jembatan ataujalan keempat dari kebuntuan ideologi gerakan oposisi pra-revolusi, yaitu antaranasionalis-sekuler, Marxis-Komunis dan Fundamentalisme Islam.Dan ideologi Syari?atimelapangkan jalan bagi diterimanya Imam Khomeini sebagai pemimpin revolusioner.Kata Kunci: revolusi Iran; syi?ah; pembebasann Syari?ati adalah kesatuan antara Tuhan,